Estimation of the areal evapotranspiration of the Ingói-berek in the Kis-Balaton wetland using Landsat-8 satellite images with two approaches - Soós, Gábor; Anda, Angéla (GEORGIKON FOR AGRICULTURE, 2025)
When examining the water balance of lakes, the measurement and determination of evaporation and transpiration are the biggest problems. Evapotranspiration - as an output parameter of water balance- is very important in case of our largest lake, Lake Balaton and the associated Kis-Balaton Protection System. The evapotranspiration of the common reed (Phragmites australis) plays a decisive ecological role in the wildlife of the marshes. In case of Kis-Balaton, common reed is a significant factor due to the extent of its stands, which exceed 2,000 hectares. The latest solutions in evapotranspiration models are remote sensing models. We have tried to estimate the areal evapotranspiration with the red and near-infrared bands (NDVI, Normalized Difference Vegetation Index) of Landsat-8 satellite images using two different approaches: the use of FAO-56 potential evapotranspiration equation with local crop coefficients and the SEBAL model.
Keywords: evapotranspiration; Landsat-8 satellite images; NDVI